Myristoylation-dependent palmitoylation of cyclin Y modulates long-term potentiation and spatial learning - Seo, Jiyeon; Hwang, Hongik; Choi, Yu ri; Jung, Sunmin; Hong, Jung-Hwa; Yoon, Bong-June; Rhim, Hye whon; Park, Mikyoung (Pergamon Press Ltd., 2022)
Many psychiatric disorders accompany deficits in cognitive functions and synaptic plasticity, and abnormal lipid modifications of neuronal proteins are associated with their pathophysiology. Lipid modifications, including palmitoylation and myristoylation, play crucial roles in the subcellular localization and trafficking of proteins. Cyclin Y (CCNY), enriched in the postsynaptic compartment, acts as an inhibitory modulator of functional and structural long-term potentiation (LTP) in the hippocampal neurons. However, cellular and molecular mecha-nisms underlying CCNY-mediated inhibitory functions in the synapse remain largely unknown. Here, we report that myristoylation located CCNY to the trans-Golgi network (TGN), and subsequent palmitoylation directed the myristoylated CCNY from the TGN to the synaptic cell surface. This myristoylation-dependent palmitoylation of CCNY was required for the inhibitory role of CCNY in excitatory synaptic transmission, activity-induced dy-namics of AMPA receptors and PSD-95, LTP, and spatial learning. Furthermore, spatial learning significantly reduced palmitoyl-and myristoyl-CCNY levels, indicating that spatial learning lowers the synaptic abundance of CCNY. Our findings provide mechanistic insight into how CCNY is clustered adjacent to postsynaptic sites where it could play its inhibitory roles in synaptic plasticity and spatial learning.